Characterization of three Pb-resistant fungi and their potential Pb2+ ions adsorption capacities - Sun, Xin (Water science and technology : a journal of the International Association on Water Pollution Research, 2018)
Bioremediation is preferred in heavy metal remediation, and the high-performance microbe is of prime importance. In the present research, three Pb-resistant microbes were isolated and growth characteristics and adsorption capacities were evaluated. The results showed that R. oryzae SD-1, T. asperellum SD-5, and M. irregularis SD-8 can grow well under 100 mg L-1 Pb2+ ions stress. There is a higher minimum inhibitory concentration (MIC) of Pb but lower MICs of Cd and Zn in T. asperellum SD-5. However, there were similar MICs of Cu among the three microbes. R. oryzae SD-1 exhibited a higher adsorption capacity and removal rate relative to the other two microbes under various Pb2+ ion levels. The Langmuir equation was fitted for the adsorption capacity of T. asperellum SD-5 and M. irregularis SD-8, and their maximum adsorption capacities were approximately 456.62 mg g-1 and 93.62 mg g-1. Moreover, the Elovich equation and the double constant equation can describe the adsorption process of Pb2+ ions in Pb-resistant microbes well. The strongest adsorption capacity under lower Pb2+ ion level was observed in M. irregularis SD-8, while the strongest adsorption capacities under higher Pb2+ ion levels were seen in R. oryzae SD-1 and T. asperellum SD-5. Therefore, three novel Pb-resistant microbes may be used as efficient, easily cultivated materials for Pb-contaminated soil remediation